The Development of Sufism and Orders in Kelantan - Abdul Ghani Muhamad; Nik Yusri Musa (Rabbanica: Journal of Revealed Knowledge)
Sufism is one of the disciplines within the Islamic scholarly civilisation. Sufism is a teaching that finds its foundation in both theory and practice. Theoretically, the formulation originates from the verses of the Quran and the Sunnah of the Prophet Muhammad (peace be upon him). In contrast, from a practical aspect, it is based on verses and hadith that encourage remembrance of Allah, the Creator and Administrator of the entire universe. Islamic scholars rooted this discipline during the golden age of material civilisation in the Islamic world. These scholars urged Muslims to remain focused on Allah SWT, the Giver of blessings (Mun'im), rather than becoming distracted by their blessings. From this foundation, they based their call on the lives of the Prophet Muhammad (peace be upon him), his companions, the tabi'in, and the atba' al-tabi'in. The Islamic world has witnessed a winding and varied development period for the discipline of Sufism, which has also impacted Nusantara, generally, and Kelantan, specifically. The objective of this study is to identify the development of Sufism and tariqat in the state of Kelantan, including its history, figures, understanding, types of tariqat, and the books used as references in the teaching of Sufism and tariqat. The research methodology was based on a qualitative approach using a bibliography, review, and analysis of documents related to the discipline of Sufism. The study results found that Sufism prevalent in Kelantan is Sunni Sufism, first introduced in the 14th century AD and spread widely in the 18th to 20th centuries AD. Currently, the rapid decline in its development coincides with the passing of the shaykhs, or teachers of the hut schools.